SCIENTIFIC AND METHODOLOGICAL APPROACHES TO THE INCORPORATION ADAPTATION POTENTIAL IN ENTERPRISE MANAGEMENT SYSTEM STRATEGIC - Zaitseva, Olena; Betina, Viktoriia (Науковий вісник Полісся, 2017)
Urgency of the research. Proved that in terms of socioeconomic transformation success of the company depends on its ability to respond quickly and effectively to external factors influence and adapt to them. It adaptive capabilities ensure strategic stability in a turbulent business environment, and this is due to the relevance of theoretical and methodological research in this area. Target setting. The article aims to study the incorporation of methodological approaches potential adaptation enterprises in strategic management to ensure business effectiveness. Actual scientific researches and issues analysis. Question enterprise adaptation to changes in the competitive environment, clarify the definitions of "adaptive capacity" of evolution and adaptation strategic management concepts are the focus of many leading academic economists Biloshkurskoyi N. V., Ivanova A. D., Stepanova J. L., Srahovych V. G., Tishchenko A. N., Harafonovoyi O. I. and others. Uninvestigated parts of general matters defining. While acknowledging the theoretical and practical values of previous research results, should determine the need to study the adaptation potential of the company in the context of strategic management to ensure business effectiveness. The research objective. To make the system adaptive concept of strategic management, which will depending on the capacity of adaptation, strength, speed and predictability of changes the company choose the appropriate strategy and behavior. The statement of basic materials. The impact of the business depends on the adaptive capacity and level of development of the region for the location of businesses and industry specifics. Potential adaptation - a multicomponent set of enterprise resources that allow it to adapt to a dynamic environment and are crucial for the realization of opportunities and avoid threats or warnings. Depending on the value of adaptive capacity, sensitivity and willingness of enterprises to respond to the challenges of internal and external environment company chooses adaptation strategy and model behavior: active, passive, situational. Conclusions. In the process of incorporation adaptation capacity in strategic management in selecting strategies is necessary to determine its compatibility and a balance of external conditions and internal capabilities of the enterprise. Depending on the level of adaptation capacity, speed, scale and predictability of changes in the market the company chooses the appropriate strategies and behaviors.